UJI TOKSISITAS EKSTRAK DAUN TEMBAKAU (Nicotiana tobacum L.) DENGAN METODE MASERASI TERHADAP MORTALITAS LARVA Culex quinquefasciatus Say. DI LABORATORIUM - Merry Putri Wijayanti; Sri Yuliawati; Retno Hestiningsih (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2015)
Culex quinquefasciatus Say. is the main vectors in the transmission of filariasis disease in Indonesia. The use of plant-based insecticide is an alternative to reduce the negative impact of chemical insecticides. One of them is by using tobacco leaf extract. The purpose of this study was to determine the deadly power of tobacco leaf extract (Nicotiana tobacum L.) on mortality of larvae Culex quinquefasciatus Say. The type of this research is an experimental research with Posttest Only Control Group Design. The parameters observed are mortality of LC50 and LC90 larvae Culex quinquifasciatus Say. by using probit regression analysis. The population were all larvae Culex quinquefasciatus Say. instar III. The data analysis technique is by using One-Way Anova testing followed by the Games-Howell test. The results of this study indicate that LC50 and LC90 concentrations of tobacco leaf extracts are 0.058% and 0.095%. Based on One-Way Anova test is known that p value = 0.001 (p <0.05). Games-Howell test results shows that the concentrations of 0.031%, 0.066%, and 0.095% have significant differences in the average mortality of larvae due to having a different letter notation. From this research results, it can be concluded that the tobacco leaves extract (Nicotiana tobacum L.) has a deadly power to larvae Culex quinquefasciatus Say. as larvicides. However, the need for further research regarding the killing power of tobacco leaf extract in the ratio of the amount of time the extract.